Gereja sebagai Tempat Pemulihan: Strategi Pastoral dalam Melayani Jemaat yang Terjerat Okultisme - Wicaksono, Arif; Pranowo, Rebecca Glorya (KHAMISYIM: Jurnal Teologi dan Pendidikan Kristiani, 2025)
The church plays a crucial role as a place of restoration for individuals trapped in occult practices. This study employs a descriptive qualitative method with a literature study approach to analyze pastoral strategies in addressing this phenomenon. Three main strategies identified are doctrinal education, holistic pastoral care, and deliverance prayer ministry. Doctrinal education aims to strengthen congregants’ understanding of the dangers of occultism and God’s power. Holistic pastoral care provides spiritual, psychological, and social guidance for individuals seeking to break free from spiritual bondage. Meanwhile, deliverance prayer plays a role in freeing individuals from dark influences through the authority of Christ. This study highlights that the church must be proactive in educating, guiding, and restoring affected congregants while avoiding sensationalism in deliverance ministry. With a holistic approach based on God’s word, the church can effectively serve as a place of healing for those seeking to return to a Christ-centered life.Abstrak Gereja memiliki peran penting sebagai tempat pemulihan bagi individu yang terjerat dalam praktik okultisme. Studi ini menggunakan metode kualitatif deskriptif dengan pendekatan studi pustaka untuk menganalisis strategi pastoral dalam menangani fenomena ini. Tiga strategi utama yang diidentifikasi adalah pendidikan doktrinal, pendampingan pastoral yang holistik, dan pelayanan doa pelepasan. Pendidikan doktrinal bertujuan memperkuat pemahaman jemaat mengenai bahaya okultisme dan kuasa Tuhan. Pendampingan pastoral memberikan bimbingan spiritual, psikologis, dan sosial bagi individu yang ingin melepaskan diri dari keterikatan spiritual. Sementara itu, doa pelepasan berperan dalam membebaskan individu dari kuasa gelap melalui otoritas Kristus. Studi ini menekankan bahwa gereja harus aktif dalam mendidik, membimbing, dan memulihkan jemaat yang terdampak, serta menghindari praktik sensasionalisme dalam pelayanan pelepasan. Dengan pendekatan yang holistik dan berbasis pada firman Tuhan, gereja dapat menjadi tempat pemulihan yang efektif bagi mereka yang ingin kembali kepada kehidupan yang berpusat pada Kristus.Kata kunci: Gereja, Okultisme, Pastoral, Pemulihan, Doa Pembebasan